Benefits of aquatic exercise during pregnancy: A systematic review - Zajmi, Elga; Misja, Bardhy (Sustainability and Sports Science Journal, 2026)
Aquatic exercise has emerged as an accessible form of prenatal physical activity due to its reduced musculoskeletal load and improved thermoregulation. Growing evidence suggests potential benefits for maternal well-being as well as pregnancy- and birth-related outcomes. Objectives: To synthesize current evidence on the effects of aquatic exercise during pregnancy on maternal health and labour outcomes. Methods: A systematic review was conducted using PubMed and Google Scholar to identify studies published between 2020 and 2025 investigating aquatic exercise or hydrotherapy interventions in pregnant women. Eligible studies included randomized controlled trials, clinical trials, and systematic reviews/meta-analyses published in English. Data extracted included study design, participant characteristics, intervention protocols, and maternal and labour-related outcomes. Results: Five studies met the inclusion criteria. Findings from randomized controlled trials and meta-analyses suggest that aquatic exercise during pregnancy may improve maternal mental health, reduce perceived labour pain, enhance quality of life, and support gestational weight management. No adverse neonatal outcomes were reported in the included studies. However, findings related to mode of delivery and obstetric outcomes were limited and inconsistent. Conclusions: Aquatic exercise may be a useful component of prenatal care and may provide benefits for maternal well-being. However, conclusions should be interpreted with caution due to the limited number of studies and heterogeneity of the available evidence. Further high-quality, large-scale studies are needed to strengthen the evidence base.